Effects of increased respiratory resistance on maximal O2 uptake and anaerobic threshold during incremental exercise tests - Özçel?k, Oöuz; Çolak, Ramis (My University, 2002)
This study was undertaken to assess whether maximal O2 uptake (VO2max) can be used as an index of measuring aerobic capacity under the condition of increased respiratory resistance. Seven male subjects performed two incremental exercise tests on a cycle ergometer on different days: one control (C) and one breathing through an 8 mm bore diameter respiratory resistance (R). Ventilatory and gas exchange responses were measured with a turbine volume transducer and mass spectrometry, and processed breath-by-breath. VO2max was measured and anaerobic threshold (AT) was estimated noninvasively using the V-slope method. Maximal exercise performance was reduced significantly (by paired t-test, P<0.05) in the resistance study (233±14 W) compared to the control (260±29 W). The plateau in VO2 is not a consistent feature of incremental exercise tests even in the control study at the subjects' maximum effort. VO2 at maximal exercise performance was also reduced significantly from 3.25±0.40 1/min (C) to 2.83±0.20 1/min (R). However, there were no significant differences between AT for both tests: 1.80±0.28 1/min (C) and 1.81±0.28 1/min (R). These results establish that AT actually reflects aerobic capacity. Therefore, AT should be determined systematically in addition to VO2max during maximal exercise tests to better evaluate physical fitness.
Keywords: Anaerobic threshold; Exercise test; O2 uptake